Muscle protein synthesis in response to nutrition and exercise - Atherton, P. J.; Smith, K. (The Journal of Physiology, 2012)
Muscle protein synthesis (MPS) is the driving force behind adaptive responses to exercise and represents a widely adopted proxy for gauging chronic efficacy of acute interventions, (i.e. exercise/nutrition). Recent findings in this arena have been progressive. Nutrient-driven increases in MPS are of finite duration (~1.5 h), switching off thereafter despite sustained amino acid availability and intramuscular anabolic signalling. Intriguingly, this `muscle-full set-point' is delayed by resistance exercise (RE) (i.e. the feeding × exercise combination is `more anabolic' than nutrition alone) even >24 h beyond a single exercise bout, casting doubt on the importance of nutrient timing vs. sufficiency per se. Studies manipulating exercise intensity/workload have shown that increases in MPS are negligible with RE at 20-40% but maximal at 70-90% of one-repetition maximum when workload is matched (according to load × repetition number). However, low-intensity exercise performed to failure equalises this response. Analysing distinct subcellular fractions (e.g. myofibrillar, sarcoplasmic, mitochondrial) may provide a readout of chronic exercise efficacy in addition to effect size in MPS per se, i.e. while `mixed' MPS increases similarly with endurance and RE, increases in myofibrillar MPS are specific to RE, prophetic of adaptation (i.e. hypertrophy). Finally, the molecular regulation of MPS by exercise and its regulation via `anabolic' hormones (e.g. IGF-1) has been questioned, leading to discovery of alternative mechanosensing-signalling to MPS.